Metamorphoses of Corruption and Post-Socialist transformation of Public and Private Spheres in Bulgaria (UNWE Yearbook, 2014)
The study is focused on two characteristic processes in the Bulgarian post-socialist society and their interrelationship: the transformation of the public and private sectors and the dynamics of the accompanying corruption practices. A specific perspective towards the analysis of corruption is suggested – it is conceived as a key element of different social groups’ strategies, pursueing their private, group or corporate political and economic interests, as well as acquirement, preservation and conversion of political and economic power. First, the study traces the main phases of the post-socialist transformations in terms of systematic change in the public-private configurations. Then, the corruption is conceptualised as an illegitimate quasi market exchange between the actors in the public and private sectors and a working definition of corruption is suggested. The stress is put on the so called “grand” corruption and a general political-economic model of the corruption related networks “state – political parties – business” of oligarchic nature is presented. More specific attention is given to the most spread  and highly socially sensitive corruption practices related to privatisation of the state property, “black” and “grey” economy, public procurement and concessions, management of public financial and industrial  assests, utilisation of the EU structural and cohesion funds.  In conclusion, some basic directives for reducing corruption in Bulgaria are formulated.